Perbandingan Hukum Taiwan-Indonesia Berbasis Prinsip CEDAW dalam Upaya Perlindungan PMI Perempuan - Nurul Atika, Biyes; Azani, Adila; Claudilla Putri, Rizha (UNIB Press, 2025)
Various cases of violence, gender discrimination, difficulty in accessing health care and exploitation of migrant workers still occur frequently, especially against women working in the non-formal sector. BP2MI noted that Taiwan is the number 2 highest destination country for PMI after Hong Kong. Indonesia as a member state of the United Nations has ratified CEDAW while Taiwan, which is not a member of the United Nations, has not ratified the convention. This is a challenge in the protection of female migrant workers in Taiwan. Thisstudy comparing the regulation of migrant workers within the legal framework of Taiwan and Indonesia in relation to CEDAW as well as the Indonesian government's efforts to protect migrant workers in the non-formal sector in Taiwan. This type of research is juridical-normative research, the nature of this research is descriptive analytical with a method of approaching laws and regulations and conceptual related to the research topic. The results of the study found that Indonesia tends to emphasize more on comprehensive protection starting from the preplacement process to repatriation and strengthened by the role of BP2MI, emphasizing on aspects of reproduction, gender-based violence, and protection of women from exploitation. Meanwhile, Taiwan emphasizes technical protection during the working period and still faces challenges in providing protection to female migrant workers in the non-formal sector because they have not been accommodated in labor.